The Problem of Defining ‘Indigenous Literacy:’ Lessons from the Andes - Browning, Peter (Íkala, Revista de Lenguaje y Cultura, 2016)
Since the United Nations included literacy in its Millennium Development Goals, the importance of literacy has secured its place in the collective consciousness as a central marker of development, and discussions of ‘indigenous literacy’ have become commonplace. This article touches upon some of the problems of defining ‘indigenous literacy’ with explicit reference to the Quechua-speaking Andean region. Section 1 begins to unpack the terms ‘literacy’ and ‘indigenous’ in order to better understand the question posed. Section 2 (Colonial Literacy) considers literary practice in the colonial period: it will be seen that both the technology introduced (the European alphabetic script) and the form this took (the book) circumscribed pre-Columbian literary practice. Section 3 (Standardization of Quechua) is concerned with how the technology introduced continues to affect literacy practices, as will be shown through the debate surrounding the standardization of the Quechua alphabet. Finally, section 4 (‘Social Literacies’) considers a ‘social literacy’ orientation illustrating how such an approach can help us move beyond an entrenched, traditional concept of ‘literacy’ and look not only at literacy as a social practice as it is enacted by social actors, but also to involve those actors in the very definition of what they consider to be ‘literacy practice.’